NEED FOR INNOVATION OF PROTECTION WORK OF THE IDEOLOGICAL BACKGROUND OF THE COMMUNIST PARTY OF VIETNAM IN THE CURRENT SITUATION - Vy, Trinh Yen (American International Journal of Social Science Research, 2022)
The study examines the need to innovate protection work of ideological background of the Communist Party of Vietnam in the current situation. The Platform for National Construction in the Transitional Period to Socialism (Added and developed in 2011), the 2013 Constitution, and many documents of the Party congresses have affirmed: “The Party takes Marxism-Leninism and Ho Chi Minh's thought as the ideological foundation and a guideline for action". This affirmation is consistent with the revolutionary practice of Vietnam over the past 90 years under the leadership of the Communist Party of Vietnam. It has proven that by perseveringly following the path of Marxism-Leninism and Ho Chi Minh’s thoughts, Vietnam has achieved many impressive achievements and is increasingly developing in the cause of renovation. The study employs scientific research methods such as analysis, synthesis, logic, history, and comparison. The study shows that the requirement for renewal of the protection of the Party's ideological foundation, for the time being, is more urgent and significant than ever as hostile forces are always aggressive, intensifying activities against the ideological foundation of our Party and State. JEL Classification Codes: D72.